2021
DOI: 10.32598/rj.22.1.3287.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Employment Status and Occupation Type on Occupational Stress and General Health of Physically Disabled Employees in Vocational Centers of the State Welfare Organization of Tehran: A Cross-Sectional Study

Abstract: Objective: Disabled people experience worse situation in respect of the stress, health, and socio-demographic indicators than healthy people. Little knowledge is available about the way in which this disadvantage is patterned by employment status and occupation type, especially in employees with physical disabilities. Few studies have investigated the potential effect of employment status and occupation type on general health and occupational stress in physically disabled employees. This study investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These issues not only affect people with disabilities, but include their friends, relatives, and almost all people in the society (Villanueva-Flores et al, 2014 ). People with disabilities face socio-economical inequalities, communicative limitations, and physical barriers in order to enter the labor market and experience higher stress and worse health status compared to normal people (Ghaneh-Ezabadi et al, 2021 ). Therefore, employment as a mechanism to compensated physical and social limitations of people with disabilities, rebuilding their daily lives and improving their life quality, plays an important role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues not only affect people with disabilities, but include their friends, relatives, and almost all people in the society (Villanueva-Flores et al, 2014 ). People with disabilities face socio-economical inequalities, communicative limitations, and physical barriers in order to enter the labor market and experience higher stress and worse health status compared to normal people (Ghaneh-Ezabadi et al, 2021 ). Therefore, employment as a mechanism to compensated physical and social limitations of people with disabilities, rebuilding their daily lives and improving their life quality, plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for selecting academic buoyancy, employability, and mental health in quantitative part is that studies in Iran show people with disabilities suffer from problems regarding these variables (Binaei Khajekini et al, 2022 ; Fayazi et al, 2019 ; Ghaneh-Ezabadi et al, 2021 ) that most of these studies were in-person counseling and psychotherapy and limited studies have been conducted on these people as online studies. Moreover, different studies have shown that digital storytelling can lead to better teaching and learning in terms of career, academic, and clinical aspects.…”
Section: Introductionmentioning
confidence: 99%